AKTIVITAS ANTIFUNGI EKSTRAK ETANOL BATANG BINAHONG (Anredera cordifolia (Tenore) Steen.) TERHADAP Candida albicans SERTA SKRINING FITOKIMIA - Kumalasari, Eka; Sulistyani, Nanik (Pharmaciana, 2011)
Anredera cordifolia is a plantused as antifungal empirically. This study aims tofind out the antifungal activity of ethanol extract of A. cordifolia stem against C.albicans and to identify the chemical subtance groups of the ethanol extract of A.cordifolia. The A. cordifolia stem was extracted by maceration method using ethanol 70% as solvent. The antifungal assay was done using liquid dilution method with variousconcentrations of (85; 86; 87; 88; 89; 90% w/v). The mixtures of extract and suspensionof C. albicans in CYG (Casein Yeast Glucose) medium and the media were incubated at37ÂºC for 18-24 hours to determine Minimum Inhibitor Conceration (MIC).Theculturewas streaked on SDA (Sabouraud Dextrose Agar) medium to determineMinimum Fungicidal Conceration (MFC). Chromatographic test and tube test weredone to identify the chemical substances of A. cordifolia extract. The result showed thatthe MIC could not be determined because the extract was brownish and turbid while theMFC of A. cordifolia stem ethanolic extract was 86% w/v. The result of thephytochemical screening with tube test and the thin layer chromatography test showedthat the extract of A. cordifolia stem contained flavonoids, polyphenols, and saponin.